Antioxidant and Neuroproliferative Effects of THL-3-PTD5 Peptide Derived from Hydramacin-1 Antimicrobial Peptide - Ping-Chien Lee; Ching-Chun Lin; Hui-Hsuan Hsu; Feng-Di T. Lung (Journal of Chemistry)
Parkinson’s disease (PD) is a neurodegenerative disorder characterized by reduced dopamine levels in the brain, affecting over 6 million people worldwide. While current treatments for patients primarily focus on symptom relief, there is a necessity for the development of novel therapeutic agents due to the presence of side effects and declining effectiveness. Functional peptides, known for their high selectivity, specificity, and diverse bioactivities, have shown the potential to develop therapeutic candidates for neurodegenerative diseases. Notably, the macin family of proteins exhibits potent antimicrobial activity and nerve repair effects. In this study, we investigated the antioxidant activity and neuroproliferative effects of a series of truncated peptides (THL, THL-1, THL-2, and THL-3) derived from the C-terminal sequence of hydramacin-1. Results showed that THL-3 exhibited the strongest antioxidant activity (EC50 of 22.5 μM) in ABTS-radical scavenging assays, with amino acid residues Cys5, Pro6, Leu7, Lys9, and Lys10 playing critical roles in its activity. Upon conjugation with the cell-penetrating PTD5 peptide to form THL-3-PTD5, it exhibited a significant dose-dependent neuroproliferative effect, increasing the viability of SH-SY5Y cells by 118% at 100 μM. However, it did not exhibit neuroprotective effects under in vitro conditions of oxidative stress induced by an exogenous oxidizing agent. This study suggests that THL-3-PTD5 may serve as a potential candidate for developing therapeutic agents against neurodegenerative diseases.